An Overview Of Sports Engineering: History, Impact And Research - Anwar, P. P. Abdul Majeed; Zahari, Taha; Mohd Hasnun Ariff, Hassan; Mohd Azri, Aris; Nina Nadia, Sahim (Kementerian Pendidikan Malaysia, 2013)
Sports engineering can be considered as a new engineering discipline. It bridges the gap between two distinctive fields: sport science and engineering. Sports engineers are responsible in designing and building new equipment based on athlete’s demands, besides measuring the performance of the athlete, the equipment itself, as well as their interaction. It is without doubt that engineering and technology have played an important role not only in improving the performance of an athlete, but also in making sports more entertaining and safe. This article provides an insight into how engineering and technology have affected sports in many ways transforming it from just a past time to more exciting and competitive world events. Apart from the impact of engineering in sports, the history of the application of engineering and technology in sports is also elaborated. Furthermore, research conducted in related fields worldwide is highlighted. A brief overview of sports engineering research in Malaysia is also presented.